Targeting lactate metabolism for cancer immunotherapy - a matter of precision. (January 2023) - Heuser, Christoph; Renner, Kathrin; Kreutz, Marina; Gattinoni, Luca
Abstract: Immune checkpoint inhibitors and adoptive T cell therapies have been valuable additions to the toolbox in the fight against cancer. These treatments have profoundly increased the number of patients with a realistic perspective toward a return to a cancer-free life. Yet, in a number of patients and tumor entities, cancer immunotherapies have been ineffective so far. In solid tumors, immune exclusion and the immunosuppressive tumor microenvironment represent substantial roadblocks to successful therapeutic outcomes. A major contributing factor to the depressed anti-tumor activity of immune cells in tumors is the harsh metabolic environment. Hypoxia, nutrient competition with tumor and stromal cells, and accumulating noxious waste products, including lactic acid, pose massive constraints to anti-tumor immune cells. Numerous strategies are being developed to exploit the metabolic vulnerabilities of tumor cells in the hope that these would also alleviate metabolism-inflicted immune suppression. While promising in principle, especially in combination with immunotherapies, these strategies need to be scrutinized for their effect on tumor-fighting immune cells, which share some of their key metabolic properties with tumor cells. Here, we provide an overview of strategies that seek to tackle lactate metabolism in tumor or immune cells to unleash anti-tumor immune responses, thereby opening therapeutic options for patients whose tumors are currently not treatable.